Expanded autologous regulatory T-lymphocyte infusions in ALS: A phase I, first-in-human study. Issue 4 (July 2018) - Thonhoff, Jason R.; Beers, David R.; Zhao, Weihua; Pleitez, Milvia; Simpson, Ericka P.; Berry, James D.; Cudkowicz, Merit E.; Appel, Stanley H.
Abstract : Objective: To determine whether autologous infusions of expanded regulatory T lymphoctyes (Tregs) into patients with amyotrophic lateral sclerosis (ALS) are safe and tolerable during early and later stages of disease. Methods: Three patients with ALS, with no family history of ALS, were selected based on their differing sites of disease onset and rates of progression. Patients underwent leukapheresis, and Tregs were subsequently isolated and expanded ex vivo. Tregs (1 × 10 6 cells/kg) were administered IV at early stages (4 doses over 2 months) and later stages (4 doses over 4 months) of disease. Concomitant interleukin-2 (2 × 10 5 IU/m 2 /injection) was administered subcutaneously 3 times weekly over the entire study period. Patients were closely monitored for adverse effects and changes in disease progression rates. Treg numbers and suppressive function were assayed during and following each round of Treg infusions. Results: Infusions of Tregs were safe and well tolerated in all patients. Treg numbers and suppressive function increased after each infusion. The infusions slowed progression rates during early and later stages of disease. Spearman correlation analyses showed that increased Treg suppressive function correlated with slowing of disease progression per the Appel ALS scale for each patient: patient 1: ρ (rho) = −0.60, p = 0.003; patient 2: ρ = −0.71, p = 0.0026; and patient 3: ρ = −0.54, p = 0.016. Measures of maximal inspiratory pressure also stabilized, particularly in 2 patients, during Treg infusions. Conclusions: These results demonstrate the safety and potential benefit of expanded autologous Treg infusions, warranting further clinical trials in patients with ALS. The correlation between Treg suppressive function and disease progression underscores the significance of using Treg suppressive function as an indicator of clinical status. Classification of evidence: This study provides Class IV evidence. This is a phase I trial with no controls.